New onset of mental disorders, lifestyle changes, and quality of relationships during COVID-19 in italian population. (13th April 2021) - Caldirola, D.; Cuniberti, F.; Daccò, S.; Defillo, A.; Lorusso, S.; Perna, G.
Abstract : Introduction: The COVID-19 pandemic has been causing relevant public health and psychosocial consequences. Objectives: To assess the impact of the COVID-19 pandemic on mental health, lifestyle and personal relationships in the Italian general population. Methods: An online survey spread between May and June 2020 to collect socio-demographic, clinical, lifestyle, relationship, and mental health self-reported information. Mental disorder screening was performed by the Patient Health Questionnaire and PTSD Checklist for DSM-5. Results: Participants were 2003, 1504 of which (75%) completed the entire questionnaire (1157 females, 77%). Among the completers who have not had any mental disorder before (n=524, 35%), 263 (51.7%) met cut-off scores for psychiatric diagnoses on the self-report psychiatric screeners during the pandemic (i.e., Major Depressive Disorder, 11.3%, with death thoughts in approximately half of the cases; Panic Disorder, 1.1%; Generalized Anxiety Disorder, 13%.3, Obsessive-Compulsive Disorder, 13.2%, Post-Traumatic Stress Disorder, 7.3%; Alcohol Abuse, 5.5%). In line with this, 39% of completers complained of insomnia, while 12% and 10% started using anxiolytics and antidepressants, respectively. Approximately 7-8 % of completers started/increased alcohol and/or nicotine consumption, 33% quitted/decreased physical activity, and 40% declared decreased sexual satisfaction. Approximately 21% and 38% declared worsening in relationship with partner and difficulty in child-caring, respectively. Conclusions: The COVID-19 pandemic appears to be a risk factor for new onset of mental disorders and worsening in lifestyle and familial relationships in the Italian population. These results should be confirmed by clinical interviews, and may represent a starting point for further monitoring of the medium and long-term consequences of the COVID-19 pandemic. Disclosure: No significant relationships.